Beyond day and night: The importance of ultradian rhythms in mouse physiology - Vojtěch Škop; Naili Liu; Cuiying Xiao; Emma Stinson; Kong Y. Chen; Kevin D. Hall; Paolo Piaggi; Oksana Gavrilova; Marc L. Reitman (Elsevier, 2024)
Our circadian world shapes much of metabolic physiology. In mice ∼40% of the light and ∼80% of the dark phase time is characterized by bouts of increased energy expenditure (EE). These ultradian bouts have a higher body temperature (Tb) and thermal conductance and contain virtually all of the physical activity and awake time. Bout status is a better classifier of mouse physiology than photoperiod, with ultradian bouts superimposed on top of the circadian light/dark cycle. We suggest that the primary driver of ultradian bouts is a brain-initiated transition to a higher defended Tb of the active/awake state. Increased energy expenditure from brown adipose tissue, physical activity, and cardiac work combine to raise Tb from the lower defended Tb of the resting/sleeping state. Thus, unlike humans, much of mouse metabolic physiology is episodic with large ultradian increases in EE and Tb that correlate with the active/awake state and are poorly aligned with circadian cycling.